Pengaruh Pembelajaran STAD berbantuan Papan Kartu pada Materi Vektor SMA terhadap Komunikasi Matematis Siswa - Fitri Umardiyah; Lintang Prameswari; Wisnu Siwi Satiti (Griya Journal of Mathematics Education and Application, 2024)
This research was conducted with the aim of finding out the effect of STAD learning assisted by card boards on vector material on the mathematical communication skills of class X students at MAN 9 Jombang. This research uses a quantitative approach with the Intact-Group Comparison type Pre-Experimental Designs method. The subjects of this research were class X students of MIA MAN 9 Jombang. The research instruments used were lesson plan implementation observation sheets, oral communication observation sheets, card board questions, and test questions as the main instruments. As well as learning implementation plans (RPP) and questionnaires as supporting data. The test instrument consists of five questions about vectors for students' written mathematical communication skills. Then the oral communication observation sheet contains statements that are used to determine students' oral mathematical communication abilities. The data analysis technique used is hypothesis testing. Before testing the hypothesis, the data obtained is first tested for normality. Based on the calculation of the independent sample t test, it shows that the significance value is <0.001, the significance is <0.05, so it can be concluded that Ho is rejected and Ha is accepted. This shows that STAD learning assisted by card boards on vector material has an effect on students' mathematical communication skills.